The Use of Reference Markers (it, this, and that) and Their Relation to the Pedagogical Context - Dirham, Ulfah Ridhwan; Suwandi, Sahri; Baron, Rifari; Nugroho, Nugroho (Universitas Muhammadiyah Mataram, 2025)
The study focuses on the purposes and ramifications of reference markers (it, this, and that) for teaching English in educational situations by analyzing their usage in 10 articles from Newsweek and Tempo News. The study examined the ways in which these indicators support textual coherence in professional writing using a qualitative research approach and content analysis. The information came from eleven pieces that were published for Tempo News and Newsweek. According to the results, reference markers had a less substantial role in the texts under analysis than anticipated; Newsweek had more occurrences of reference markers than Tempo News. This disparity shows that reference markers may be used differently based on target audience, writing style, and cultural norms. The study also raises the possibility of a disconnect between theoretical knowledge and real-world text application. In order to fill these gaps, teachers should enhance their understanding of successful teaching and learning reference marker tactics by incorporating real materials into their lessons and assessing students' competency levels.